2021
DOI: 10.1021/acs.orglett.0c03735
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Chemoselective Alkylation of Tryptophan-Containing Peptides

Abstract: We report a photochemical method for the chemoselective radical functionalization of tryptophan (Trp)-containing peptides. The method exploits the photoactivity of an electron donor–acceptor complex generated between the tryptophan unit and pyridinium salts. Irradiation with weak light (390 nm) generates radical intermediates right next to the targeted Trp amino acid, facilitating a proximity-driven radical functionalization. This protocol exhibits high chemoselectivity for Trp residues over other amino acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…A final example 285 illustrates the use of charge-transfer complexes for the C2 alkylation of tryptophan residues 966 (Scheme 255). Here pyridinium salts 967 act as electron-poor p-systems that can complex with the electron-rich p-system of indoles, as in tryptophan.…”
Section: Charge Transfer Complexesmentioning
confidence: 99%
“…A final example 285 illustrates the use of charge-transfer complexes for the C2 alkylation of tryptophan residues 966 (Scheme 255). Here pyridinium salts 967 act as electron-poor p-systems that can complex with the electron-rich p-system of indoles, as in tryptophan.…”
Section: Charge Transfer Complexesmentioning
confidence: 99%
“…Based on the above experiment results and previous studies, a plausible reaction pathway for the deaminative cross-coupling of Katritzky salts with silyl enol ethers is depicted in Figure . Initially, silyl enol ethers 1 could interact with Katritzky salts 2 to form the EDA complex A , which could be activated by visible light (427 nm LEDs) irradiation to induce a SET process and deliver the radical ion pair ( B and C ).…”
Section: Resultsmentioning
confidence: 52%
“…In 2018, pioneering studies have been reported independently by the groups of Aggarwal and Glorius that the Katritzky salt of available primary amines could act as an electron acceptor for the formation of EDA complexes with bis-(catecholate)­diboron (B 2 cat 2 ) in the dimethylacetamide (DMA) solvent, which provided rapid catalyst-free access to boronic esters under the irradiation of blue light-emitting diodes (LEDs). By employing this strategy, different electron donors ( D ) have been explored to form the EDA complexes with Katritzky salts, and a series of C–C­(sp 3 ), C–C­(sp 2 ), and C–S bond formation methods has been well developed by the groups of Xu, Melchiorre, and Liao (Figure b). Very recently, Melchiorre and co-workers reported the redox-neutral addition of alkyl radicals to silyl enol ethers via the EDA complex, but organic catalysts were needed as electron donors for the catalytic EDA complex formed (Figure c) …”
Section: Introductionmentioning
confidence: 99%
“…8,9 Photoredox catalysis strategies for developing novel, complex molecules have recently become more popular, and breakthroughs compared with a traditional synthesis methodology appear to be likely. 10 For example, Taylor 11 and Melchiorre 12 recently reported on a photochemical process for the selective modification of tryptophan residues in peptides and small proteins by utilizing N-carbamoylpyridinium salts and light irradiation. tryptophan-containing peptides coupled to aryloxyamides to generate a series of N-(indol-2-yl)amide compounds (Scheme 1B).…”
mentioning
confidence: 99%
“…Over the last several decades, C–H functionalization has experienced growth, and several reports of late-stage functionalization (LSF) that could be useful for the modification of small-molecule drugs and bioactive peptides have appeared. , Photoredox catalysis strategies for developing novel, complex molecules have recently become more popular, and breakthroughs compared with a traditional synthesis methodology appear to be likely . For example, Taylor and Melchiorre recently reported on a photochemical process for the selective modification of tryptophan residues in peptides and small proteins by utilizing N -carbamoylpyridinium salts and light irradiation. Herein we report on the photoredox late-stage C–H amidation of N-unprotected indole derivatives and tryptophan-containing peptides coupled to aryloxyamides to generate a series of N -(indol-2-yl)­amide compounds (Scheme B).…”
mentioning
confidence: 99%